2021
DOI: 10.3390/app11010396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Possibility of Replacing Fly Ash with Glass Powder in Lower-Strength Concrete Mixes

Abstract: This article presents the results of research on the possibility of replacing fly ash with recycled waste glass in lower-strength concrete mixes. The results of testing concrete mixes containing either waste-glass powder or fly ash are presented in the article. A standard C12/15 concrete mix was chosen for the tests based on its common use for producing concrete for footings to support road kerbs and gutters along national roads in the Polish province of West Pomerania. In the first step of the testing procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The accepted research program largely comprised the description of the concrete compressive strength, water absorption and freezethaw confrontation after 25 and 100 cycles of freezing and thawing. Up to the chosen system, the features of air voids in toughened concrete were also defined [10] The outcomes displayed the production of 1-ton cement incompletely substituted by glass powder particles needs less energy than the cement somewhat substituted by limestone. In the end, conferring to research, usage of the glass powder deposit in the producing of fibres cement compounds may offer significant technical, environmental and economic assistance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The accepted research program largely comprised the description of the concrete compressive strength, water absorption and freezethaw confrontation after 25 and 100 cycles of freezing and thawing. Up to the chosen system, the features of air voids in toughened concrete were also defined [10] The outcomes displayed the production of 1-ton cement incompletely substituted by glass powder particles needs less energy than the cement somewhat substituted by limestone. In the end, conferring to research, usage of the glass powder deposit in the producing of fibres cement compounds may offer significant technical, environmental and economic assistance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tariq et al [13] identified greater resistance to chloride penetration in concrete with the incorporation of waste glass than in concrete with fly ash and justified that this is due to the continuous evolution and refinement of the pore structure, which results in better long-term transport performance of the binder system and considerable extension in terms of service-life for concrete exposed to marine environment. Jurczak and Szmatuła [14] compared the use of fly ash incorporation with waste glass in concrete and identified that there were no significant differences in terms of compressive strength for the concrete class adopted. Ahmad et al [15] identified a gain in compressive strength of 27% in concrete with the replacement of 20% cement with glass waste.…”
Section: Introductionmentioning
confidence: 99%
“…With urbanization accelerating, traditional construction techniques cannot meet the current increasing demand for housing. Prefabricated building is considered a major trend for future development because of its good seismic performance, easy construction, low greenhouse gas emissions, and high utilization of building materials [1][2][3]. As a type of enclosure system of prefabricated buildings, autoclaved lightweight concrete (ALC or AAC) panels are made of several fine aggregates (cement, sand, gypsum, aluminum powder, etc.)…”
Section: Introductionmentioning
confidence: 99%